Changes in polyphos-phoinositides content in nuclear membranes of rat liver and thymus cells under the action of cisplatin - E. S. Gevorgyan; Zh. V. Yavroyan; A. G. Hovhannisyan; N. R. Hakobyan (ՀՀ ԳԱԱ հրատ.)
The content of polyphosphoinositides in nuclear membranes of rat liver and thymus cells before and after the in vivo action of cisplatin has been studied. The percentage of monophosphoinositides was the highest (41-42% of total polyphosphoinositides) in both rat liver and thymus nuclear membrane fractions while the percentage of triphosphoinositides was the smallist: near 26%. Հետազոտվել է առնետների լյարդի և ուրցագեղձի բջիջների կորիզաթաղանթի պոլիֆոսֆոինոզիտիդների բաղադրությունը ցիսպլատինի in vivo ազդեցության դեպքում: Ցույց է տրվել, որ ստուգիչ տարբերակներում մոնոֆոսֆոինոզիտիդների տոկոսային բաղադրությունը ամենաբարձրն է (41-42 %), իսկ տրիֆոսֆոինոզիտիդներինը` նվազագույնը (մոտ 26 %) նշված հյուս-վածքների կորիզաթաղանթի պատրաստուկներում: Изучен состав полифосфоинозитидов ядерных мембран клеток печени и тимуса крыс после in vivo воздействия цисплатина. Показано, что в контрольных вариантах в препаратах ядерных мембран указанных тканей содержаниe монофосфоинозитидов наибольшее (41-42%), а содержание трифосфоинозитидов – наименьшее (примерно 26 %).
Keywords: Biology; Physiology